A Naphthalimide‐Based ND‐O‐EAc Photocatalyst for Sulfonation of Alkenes to Access β‐Ketosulfones Under Visible Light. Issue 23 (3rd June 2020) - Yang, Xiaoting; Yang, Jianjing; Yan, Kelu; Qin, Hongyun; Dong, Wenjie; Wen, Jiangwei; Wang, Hua
Abstract : The development of facile, efficient, cost‐effective, and visible light‐driven photocatalysts for organic synthetic chemistry has received increasing attention. This protocol has initially synthesized a naphthalimide‐based ND‐O‐EAc visible light photocatalyst for the sulfonation of alkenes to produce β‐ketosulfones. Compared with the current photosynthetic strategies, the newly developed catalytic system has some merits, namely high efficiency, gram‐scale preparation of low‐cost photocatalyst, no metal contamination, wide substrate scope, and green terminal oxidant of air. Moreover, the prepared photocatalyst of ND‐O‐EAc is feasible for the sulfonation reactions of androstenones. Importantly, such a photocatalysis strategy can easily realize the scale‐up synthesis for β‐ketosulfone drugs under the mild conditions up to 90 % yield. Abstract : The low‐cost, metal‐free, naphthalimide‐based ND‐O‐EAc photocatalyst for sulfonation of alkenes to access β‐ketosulfones has the advantage of high efficiency, wide substrate scope, and easy scale‐up synthesis of β‐ketosulfone drugs under mild conditions up to 90 % yield.